Employees Awareness And Utilisation Towards Employess State Insurance Scheme With Special Reference To Thrissur City - et. al., Sneha Sasidharan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Employees' State Insurance Scheme Of India Is An Integrated Social Security Scheme Customized To Provide Social Protection To Workers And Their Family Members, During The Time Of Contingencies, Such As, Sickness, Maternity And Death Or Disablement Due To An Employment Injury Or Occupational Hazard. The Provisions Of Esi Act Have Been Extended By “Appropriate, State Or Central Government. Of Establishments, Industrial, Commercial Or Agricultural Or Otherwise. The Esi Act Have Also Extended To Certain Specific Class Of Establishments, Such As, Shops, Hotels, Restaurants, Cinemas, Preview Theatres, Motors Transport Undertakings And Newspaper Establishments Etc., Employing 20 Employees Or More. The Fund Can Be Financed By Employees And Employers By A Certain Percentage From Their Wages. This Study Focus On The Awareness And Utilisation Of Esi Scheme And Its Utilisation By The Employees.